Fourier Transforms and the Fast Fourier Transform (FFT) Algorithm Paul Heckbert Feb
Notes 3, Computer Graphics 2, 15-463 Fourier Transforms and the Fast Fourier Transform (FFT) Algorithm Paul Heckbert Feb. 1995 Revised 27 Jan. 1998 We start in the continuous world; then we get discrete. De®nition of the Fourier Transform The Fourier transform (FT) of the function f (x) is the function F(ω), where: ∞ iωx F(ω) f (x)e− dx = Z−∞ and the inverse Fourier transform is 1 ∞ f (x) F(ω)eiωx dω = 2π Z−∞ Recall that i √ 1andeiθ cos θ i sin θ. = − = + Think of it as a transformation into a different set of basis functions. The Fourier trans- form uses complex exponentials (sinusoids) of various frequencies as its basis functions. (Other transforms, such as Z, Laplace, Cosine, Wavelet, and Hartley, use different basis functions). A Fourier transform pair is often written f (x) F(ω),orF ( f (x)) F(ω) where F is the Fourier transform operator. ↔ = If f (x) is thought of as a signal (i.e. input data) then we call F(ω) the signal's spectrum. If f is thought of as the impulse response of a ®lter (which operates on input data to produce output data) then we call F the ®lter's frequency response. (Occasionally the line between what's signal and what's ®lter becomes blurry). 1 Example of a Fourier Transform Suppose we want to create a ®lter that eliminates high frequencies but retains low frequen- cies (this is very useful in antialiasing). In signal processing terminology, this is called an ideal low pass ®lter. So we'll specify a box-shaped frequency response with cutoff fre- quency ωc: 1 ω ω F(ω) | |≤ c = 0 ω >ωc | | What is its impulse response? We know that the impulse response is the inverse Fourier transform of the frequency response, so taking off our signal processing hat and putting on our mathematics hat, all we need to do is evaluate: 1 ∞ f (x) F(ω)eiωx dω = 2π Z−∞ for this particular F(ω): 1 ωc f (x) eiωx dω = 2π ωc Z− 1 eiωx ωc = 2π ix ω ωc =− iωc x iωcx 1 e e− − = πx 2i iθ iθ sin ω x e e− c since sin θ − = πx = 2i ω ω c sinc( c x) = π π where sinc(x) sin(πx)/(πx).
[Show full text]